Privatization in an international mixed oligopoly: The role of product differentiation under price competition - Alessandra Chirco; Marcella Scrimitore (Economics and Econometrics Research Institute (EERI), 2017)
By developing a linear model in a two-country framework of international price competition, we show how the degree of product differentiation and the cross-country distribution of private firms affect the strategic privatization choices made by governments concerned with their own country's welfare. More particularly, the work points out that sufficiently low product differentiation may lead public ownership to be optimally chosen to restrict competition in the country with the larger number of firms, and privatization to be global welfare enhancing in this case.
Keywords: F23; L13; L32; 330; Mixed oligopoly; price competition; strategic privatization; international markets